World Bank Research Digest, Vol. 12(2) - World Bank (World Bank, Washington, DC, 2019)
This issue focuses on India and features the following articles: A Long History of World Bank Research Focusing on India; Looking Back on Two Decades of Poverty and Well-Being in India; For India's Rural Poor, Growing Towns Matter More Than Growing Cities; Weighing the Cost-Effectiveness of Strategies to Reduce Teacher Absence in India; Flies without Borders: Lessons from Chennai on Improving Municipal Public Health Services; Are Invisible Walls Inhibiting Internal Migration in India?Making It Easier to Apply for a Bank Account in India; Managing Food Price Volatility in India; Uncertainty and Inefficiency in South India's Groundwater Markets; Deliberative Inequality: A Text-as-Data Study of Village Assemblies in India; Cultural Impediments to Cooperating: A Studyof Low- and High-Caste Men in Rural India.